PENDAMPINGAN ORANGTUA DALAM MENINGKATKAN MINAT BELAJAR DARING ANAK KESETARAAN PAKET A SETARA SD - Anita Wahyuni Dewi; Agus Hasbi Noor; Prita Kartika (IKIP Siliwangi, 2023)
This study discusses the Parental Assistance Program in the Covid-19 Pandemic Period in increasing children's online learning interest in package A equivalence at PKBM Suryani for the 2019/2020 school year. Therefore, in utilizing technology, distance learning activities are carried out. And it is one of the solutions needed by educators and students during the pandemic that occurred on March 16, 2020. The most obvious technological development at this time is the development of the internet, therefore the role of parents is very important in accompanying learning at home. In the Big Indonesian Dictionary, etymologically learning is trying to gain intelligence or knowledge.This type of research is a qualitative research, with instruments of observation, interviews and documentation. Research respondents were 5 parents of students and 1 teacher. The results of this study indicate that there is an influence between the role of parents in guiding online learning in increasing interest in learning for children. So it can be concluded that in this pandemic period learning can run well with the participation of parents in guiding their children to learn online which is done at home.